Complete atrioventricular block during renal transplantation in a patient with Alport’s syndrome: case report - Ferrari, Fábio; Nascimento Junior, Paulo do; Vianna, Pedro Thadeu Galvão (São Paulo Medical Journal, 2001)
CONTEXT:Patients with Alport’s syndrome (causing 5% of end-stage renal disease) have a higher risk of heart conduction abnormalities. OBJECTIVE: To report a case of Alport’s syndrome developing complete atrioventricular block during renaltransplantation. CASE REPORT: A 21-year-old man with chronic renal failure due to Alport’s syndrome was submitted to a renal transplantation under epidural anesthesia and, during the intraoperative period, a complete atrioventricularblockwasdiagnosedandpromptly treated with a transcutaneous pacemaker. This extensivesympatheticblockcancontributetowards disturbances in the heart conduction system, particularly in patients with chronic renal disease in hemodialysis. Even in patients with a normal preoperative electrocardiogram or no conduction system disturbances, some degree of atrioventricular block, including complete atrioventricular block, can occur. In this situation, a transcutaneous pacemaker provides rapid and effective treatment in the operating room, thereby permitting the planning of a definitive treatment.